Evaluación de la aplicación de tres tipos de abonos orgánicos en dos variedades del cultivo de ajo (allium sativum L.), en el cantón Mira, provincia del Carchi”, 2018 - Álvarez Fuertes, Ernesto Aníbal (2018)
VII. SUMMARY In the present research work was carried out in the canton Mira, province of Carchi, Uyama sector; The objective of the research was to evaluate the response of three types of organic fertilizers in the performance of the cultivation of garlic (Allium sativum L.), in two varieties; with its specific objectives to determine the best treatment that is more efficient in the performance of the garlic crop, identify the best organic fertilizer in the crop and economically analyze the treatments, through a financial cost analysis. The treatments were 8 formed by the varieties of Peruvian and national white garlic, with application of three types of organic fertilizers in doses of 20g / EU, Bocashi, Vermicompost and fertilizer; It also included two witnesses that were the two varieties without application. The design that was used was the Complete Random Blocks with two factors under study (A + B). The evaluated data were: Height of plant at 30,60 and 90 days, diameter of the stem, length of the bulb, number of bulbils and yield. According to the results, it was determined that: of the Peruvian and national white varieties with application of organic fertilizers in doses of 20 gr / ue, it responded positively to the agronomic behavior; however, for plant height and stem diameter, the national variety has the best response; but for yield and economic analysis the Peruvian white variety responded adequately. It is concluded that the two varieties are good and respond very well to the types of fertilizers evaluated and applied in the research.